IMPAK INTERVENSI NON FARMASI TERHADAP PENERAPAN PRINSIP GREEN HOTEL DI SARINBUANA ECO LODGE - I Gusti Ayu Melistyari Dewi; I Gusti Agung Mirah Sanjiwani (Universitas Pendidikan Ganesha, 2022)
The development of sustainable tourism are efforts made by the government in dealing with the Covid-19 pandemic, in addition to the implementation of various non-pharmaceutical intervention policies. The green hotels concept emerged as an alternative that could be applied by accommodation providers in an effort to develop sustainable tourism. This study aims to analyze the dimensions of the Green Hotel concept and impact of non-pharmaceutical interventions on the application of green hotel concept at Sarinbuana Eco Lodge. A qualitative approach was done by conducting interviews with employees and management as well as observations. The data were analyzed using qualitative analysis using three stages, namely data reduction, data presentation, and conclusions. Green hotel concept has been implemented by several aspects such as environmentally management and hotel operations, environmentally land management, energy efficiency, water conservation, efficient use of building materials, local and products, air quality for health and control of convenience and waste management. The impact of non-pharmaceutical interventions in this ecolodge consists of several things, namely cancellation of guest arrivals, adjustment of employee work schedules, arrangement of guest activities during their stay at the ecolodge, temporary management carried out by the ecolodge owner's family. Management will improving the green hotel concept in hotel operational.